2020
DOI: 10.18494/sam.2020.2719
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Coastal City Tourism and Environmental Systems Based on Coupling Model

Abstract: The tourism industry and ecological environment are two major material systems that are mutually inductive and restrictive. For the sustainable development of coastal cities, a correct understanding of the sensitive relationship between the two systems is of great significance. The present study took the coastal city of Sanya in China as an example, and data from the period 2008-2017 was used to construct a tourism industry-ecological environment coupling coordination degree model (CCDM) of Sanya. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Current research primarily focuses on several key aspects. Firstly, there is a focus on tourism and the ecological environment [9,10]. Understanding the delicate relationship between these two elements is crucial for the sustainable development of cities; for the sustainable development of rural areas, Gajić et al, through a study of rural service quality [11] and tourist decision making [12], found two studies to improve the development of rural tourism to a certain extent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Current research primarily focuses on several key aspects. Firstly, there is a focus on tourism and the ecological environment [9,10]. Understanding the delicate relationship between these two elements is crucial for the sustainable development of cities; for the sustainable development of rural areas, Gajić et al, through a study of rural service quality [11] and tourist decision making [12], found two studies to improve the development of rural tourism to a certain extent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The benefit index of the tourism industry, economic development, and eco-environment subsystems of nine cities in the PRD from 2010 to 2019 were entered into the coupling degree and CCD calculation formulas (Formulas (10) and ( 11)) to gain the coupling degree and CCD of the TEE system (Table 4 and Figure 11).…”
Section: The Temporal Evolution Of the Ccdmentioning
confidence: 99%
“…A sound eco-environment increases the attractiveness of the destination and improves tourist satisfaction. While the worsening of eco-environment leads to a decrease in environmental quality in tourist destinations, threatening the healthy development of tourism [10]. Finally, economic growth and the ecological environment are also interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…5. Slope As one of the sensitive elements that may cause geological disasters, slope is critical to preserve water and soil, and it is also the primary factor in land use planning and control measures (Duan et al 2020).…”
Section: Landscape Dominancementioning
confidence: 99%